CONCEPTUAL STUDY OF ANTI-TOXIC ACTION OF TAGARADI AGADA ON POISONOUS INSECTS BITE: A SHORT REVIEW - Bhokare, Dr.Shruti Dinesh; Jadhav, Dr.Sandip Kondibhau (International Journal of Research -GRANTHAALAYAH, 2020)
Rapid urbanization lead to frequents encounters with wild animals and insects which leads to health hazards. Poisoning due to insect bite may warrant immediate medical attention. Tagaradi Agada is one of such agada useful in poisonous insect bite which is mentioned in ashtang sangraha uttartantra vishapratishedha adhyaya. Shloka phalashruti has mentioned its specific anti-toxic effect in makshika visha. This review is for collective information of therapeutic and pharmacological study of this agada for makshika visha poisoning.